Dimensi Simbolik Patung Megalitik Batak: Kajian Menurut Konsep Estetika Susanne Knauth Langer - Daulat Saragi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
Batak megalitic sculpture is an artifact cultured material that is product activated by ancient Batak people. This sculpture is a symbol of supporters feeling, ideas and belieft. Aesthetic theory of Susanne K. Langer calls this art as a symbol of her own: expressed symbol, being symbol. Sculpture is presented symbol of creator’s feeling so it is called living form. Aesthetic Langer opened and formed the frame of Batak Megalitic sclupture’s philosophys comprehension. This sculpture is not only as visual form but living form of build elements contruction such as belieft, status, legitimited symbol, and self image. Batak Megalitic sclupture reality is an art. Symbol, its presentation is not the objective reality but subjective reality, symbolic form which is resulted is living form.